Optimisme Siswa SMP dalam Menyelesaikan Soal Problem Solving - Nolismasari Nolismasari; Rahmah Johar; Yusrizal Yusrizal (Didaktik Matematika, 2017)
Currently, some students habitually answering questions with one answer. They only use the certain formula or certain steps to get answer. Thus, the ability of problem-solving and optimism that should have owned by students is not visible because of the habit of completing routine problem. Whereas the ability problem-solving and optimism is needed in the face of all the challenges that occur. This is becaused people who are able to solve the problem would be receive every event, whether it is good or bad events. They will seek the solution of problem faced and anticipate every possibility that occurs to the measures that have been selected. This study aims to determine (1) the ability of students to problem-solving and (2) optimism of students in problem-solving. This is qualitative research with test of problem solving and guided interview of optimism as instruments. Subject of this research is six students grade VIII of Junior High School at Peukan Pidie, Aceh. The results show that three students have good problem-solving ability, three other students have enough abilitiy in problem-solving. Optimism of students in problem-solving based on the dimensions of optimism is three students optimist at dimension PMG, three other students not optimist. One student was optimist on the dimensions of PVG, five other students not optimist. Five students are optimist on the dimensions of PSG and PMB, one student not optimist. All students are optimist on the dimensions of PVB. Two students are optimist on the dimensions of PSB, four students are not optimist